Studi Kekuatan Tekan pada Beton Ringan Berserat dengan Agregat Alwa - Andi Kusnadi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2010)
Concrete is one of the most widely used construction of civil buildings today several advantages compared other construction materials. One of the weaknesses of concrete structure is the weight per meter cubic big enough. It is very influential on the amount that dead load that will work on the building structure. Determination of dead load on the building structure can be minimized by the use of lightweight concrete. In structure concrete also has a weakness that is a low tensile strength and are brittle. How to repair these weaknesses, among others is by adding fiber to the concrete mixture. One popular type of fiber used is the steel fiber. The use of steel fiber as raw mixture in mixing concrete for building structures has not been widely used in Indonesia due to the difficult to obtain because it must be imported from overseas so it’s not economical. To overcome these problems some previous researchers have tried to use local ingredients widely available in the market with a relatively cheap price of fiber wire. Galvanized wire is the material chosen because in addition to these factors have reinforced the principle of concrete, is also a material that is easily obtained and is resistant to corrosion due to the porous nature of lightweight concrete. This study starts from the manufacture of specimen consists of cylindrical specimens 100 mm diameter 200 mm height for compressive strength. Variations of fiber used were 0%, 0.3%, 0.75%, 1%, with a length of 60 mm fiber diameter of 1 mm. The specimens are three pieces for each variation of fiber. From the test that has been performed, the values for each variation of fiber 0% ; 0,3% ; 0,75% and 1% are 21,58 MPa ; 24,00 MPa ; 24,81 MPa and 25,01 MPa The optimum values obtained on variations of fiber 1% increased 15.89% on compressive strength. It can be concluded that by adding addition galvanized wire fibers into lightweight concrete mixture is increasing the compressive strength very small.